Virtual reality and charitable giving – the role of space, presence, and attention - Ilia Gugenishvili; Anna-Greta Nyström (International Telecommunications Society (ITS), 2023)
Virtual Reality (VR) is a promising tool for nudging charitable attitudes and behavior. Still, how VR experiences are processed by users remains unclear. To ensure the future success of VR storytelling, therefore, it is critical to understand how users experience a VR story overall, and what the potential antecedents and consequences associated with it are. In this study, we address the gaps in the literature by comparing the spatial presence, attention allocation, spatial situation model, empathy, and donation behavior after viewing content using VR vs. a desktop computer. Results point to a clear phenomenological distinction between experiencing the content in these two mediums. Specifically, the VR group exhibited significantly higher spatial presence, attention allocation, spatial situation model, and empathy. Donation behavior, though, was equal. The study has implications for the theoretical knowledge of VR and charitable giving, as well as the Construal Level Theory of psychological distance. They are also helpful for businesses wishing to use VR in their marketing strategies.
Keywords: 330; virtual reality; charitable giving; empathy; spatial presence; attention allocation; spatial situation model